Teori Kultivasi dalam Perspektif Psikologi - Syafrizaldi Syafrizaldi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
Cultivation theory is a social theory that examines the long-term effects of television on audiences. Cultivation theory, developed by George Gerbner and colleagues at the University of Pennsylvania began in the late 1960s. This cultivation theory stems from several large-scale research projects entitled 'Cultural Indicators'. George Gerbner stated that every television broadcast can affect the audience who watch it. The influence caused by television is not only cognitive or affective, but also conative (behavioural). In principle, cultivation theory is related to the field of psychological theory in a behavioristic perspective, namely social learning theory and social cognition theory developed by Albert Banduran. Both of these theories assume that humans learn through observations and stimuli received from their environment. Likewise, what happens to children watching shows on television, with the senses that children will be able to process information from television. Then the information will automatically be stored in the cognitive and will ultimately affect the attitudes and behavior of children.